(untitled) (The Review of Diabetic Studies, 2025)
The management of death in pre-hospital settings presents one of the most sensitive and ethically complex tasks for paramedics. This review examines the multifaceted role of paramedics in the recognition of death, documentation of findings, and the authorization or communication of death reports before hospital transfer. Emphasis is placed on the interplay between clinical assessment protocols, legal frameworks, and emotional resilience. The review systematically explores international models and regulatory differences in pre-hospital death management, identifying best practices in training, multidisciplinary collaboration, and digital reporting systems. Findings indicate that paramedics play a pivotal role in ensuring procedural integrity, maintaining dignity for the deceased, and supporting families and emergency teams. The study concludes with a proposed strategic model for integrating standardized assessment, documentation, and authorization systems in emergency medical services (EMS) to enhance both professional accountability and societal trust.